New emergency department quality measure: From access block to National Emergency Access Target compliance. (13th October 2013) - Khanna, Sankalp; Boyle, Justin; Good, Norm; Lind, James
Abstract Objectives The study aims to investigate the effect of time of day and ED occupancy on the ability of EDs to admit or discharge patients within 4 h in accordance with the National Emergency Access Target (NEAT), and to compare this with corresponding levels of access block, the measure for ED performance before NEAT. Methods This is a retrospective analysis of 5 years of ED data from 30 reporting public hospitals in Queensland, Australia. Relationships between these and variations in time of day and occupancy were explored using a Poisson generalised linear model. The main outcome measures are cases of NEAT non‐compliance (ED length of stay >4 h for all patients [i.e. admitted and non‐admitted] leaving the ED) and access block (ED length of stay >8 h for admitted patients). Results NEAT performance is found to be dependent on hospital size, and levels vary significantly for admitted and non‐admitted patients. A higher proportion of patients breach NEAT during early mornings and low occupancy periods, a trend not observed with the previous access block metric. NEAT non‐compliance is also found to rise between 13.00 hours and 17.00 hours, a period when the proportion of access block cases typically drops. Conclusions EDs face rising levels of NEAT non‐compliance at times when corresponding access block levels have traditionally not been a concern. A higher proportion of patients breach the target during periods that would intuitively not be flagged as flow bottlenecks. The findings support the need for service level analysis and new solutions to guide workflow reform and maximise NEAT compliance.